Dead City - Ponti, James (New York : Aladdin, 2012)
Seventh-grader Molly has always been an outsider, even at New York City's elite Metropolitan Institute of Science and Technology, but that changes when she is recruited to join the Omegas, a secret group that polices and protects zombies.
Keywords: Zombies -- Juvenile fiction; Paranormal fiction; Mothers and daughters -- Juvenile fiction; Zombies -- Fiction; Supernatural -- Fiction; Mothers and daughters -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction